Analisis Yuridis Pemenuhan Hak Khusus Narapidana HIV dan AIDS Menurut UU No. 12 Tahun 1995 - Hardika Sandi; Nelvitia Purba (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Every prisoner who has received a judge's decision and has permanent legal force, his rights are guaranteed in Law no. 12 of 1995 concerning Corrections and further regulated in Government Regulation No. 32 of 1999 concerning Conditions and Procedures for Implementation of Correctional Inmates. Regarding prisoners who are infected with HIV and AIDS, they are also protected by the law, their right to continue to receive special services after carrying out a health examination and being declared to have an infectious disease that is likely to be transmitted to other prisoners. Correctional Technical Unit (UPT) there are prisoners who are infected with HIV and AIDS, this case can be found in prisoners before becoming correctional students and even being infected from prisoners when they have become correctional students. Class II A Pematang Siantar. The problems that want to be raised in this thesis are 1. How are the rights of prisoners living with HIV in Pematang Siantar Class II A Penitentiary fulfilled? 2. What are the inhibiting factors for fulfilling the rights of HIV and AIDS prisoners in Class II A Penitentiary A Pematang Siantar? 3. What are the prevention efforts for prisoners infected with HIV and AIDS? Basically, the scope of health services for prisoners has been regulated in Government Regulation Number 32 of 1999 concerning Terms and Procedures for the Implementation of the Rights of Correctional Inmates, namely as follows: a. Every prisoner and correctional student has the right to obtain proper health services; b. Each Correctional Institution is provided with a polyclinic and its facilities and provided at least 1 doctor and 1 other health worker; c. Health services are carried out by prison doctors; d. Health checks are carried out at least 1 (one) time in 1 (one) month and recorded in the health card; e. In the event that a prisoner or correctional student is sick, the head of the correctional institution immediately informs his family; f. In the event that a prisoner or correctional student has a complaint regarding his health, the doctor or other health care provider at the Correctional Institution is obliged to carry out an examination; g. Hospital health care costs. While the inhibiting factors for the fulfillment of prisoners' rights are the Correctional Institution Capacity Factor, the personnel or health worker factor, the Facility and Infrastructure Factor, the Availability of Special Medicines Factor, and the ARV consumption compliance factor. Keywords: Fulfillment, Special Rights, Prisoners, HIV, AIDS